Winners and Losers among Skilled Migrants: The Case of Post-Accession Polish Migrants to the UK - Pawel Kaczmarczyk; Joanna Tyrowicz (Institute for the Study of Labor (IZA), 2015)
We test if migration leads to increased wages. We take the example of Polish migrants to the United Kingdom and focus on the mobility of well educated Poles. We offer insights into absolute and relative change in wages of the migrants, utilizing the data from the UK and Polish labor force surveys. We find that while overall the returns to migration are low, they are negligible or even insignificant for the highly skilled migrants from Poland to the UK. These results hold for both absolute and relative measures.
Keywords: J24; J31; J61; 330; mobility of the highly educated; return to human capital; relative deprivation; Propensity Score Matching